COMPARATIVE COMPRESSION OF WAVELET HAAR TRANSFORMATION WITH DISCRETE WAVELET TRANSFORM ON COLORED IMAGE COMPRESSION - Christnatalis, Christnatalis; Bachtiar, Bachtiar; Rony, Rony (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2020)
In this research, the algorithm used to compress images is using the haar wavelet transformation method and the discrete wavelet transform algorithm. The image compression based on Wavelet Wavelet transform uses a calculation system with decomposition with row direction and decomposition with column direction. While discrete wavelet transform-based image compression, the size of the compressed image produced will be more optimal because some information that is not so useful, not so felt, and not so seen by humans will be eliminated so that humans still assume that the data can still be used even though it is compressed. The data used are data taken directly, so the test results are obtained that digital image compression based on Wavelet Wavelet Transformation gets a compression ratio of 41%, while the discrete wavelet transform reaches 29.5%. Based on research problems regarding the efficiency of storage media, it can be concluded that the right algorithm to choose is the Haar Wavelet transformation algorithm. To improve compression results it is recommended to use wavelet transforms other than haar, such as daubechies, symlets, and so on.